2020
DOI: 10.1002/1348-9585.12153
|View full text |Cite
|
Sign up to set email alerts
|

A moderated mediation analysis of occupational stress, presenteeism, and turnover intention among occupational therapists in Korea

Abstract: Objectives Presenteeism is undoubtedly a widespread phenomenon in organizations. Research on presenteeism has been conducted for decades in the broader workforce (eg, nurses, doctors, teachers, police officers). Occupational stress and turnover intention in occupational therapy have been extensively studied. However, the effect of presenteeism on the relationship between occupational stress and resultant turnover intention among occupational therapists is unclear. This study aims to explore the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
6
9
0
1
Order By: Relevance
“…This study found that occupational stress is associated with presenteeism, which is consistent with the results of previous studies (Chun & Song, 2020;Umann et al, 2014;Yi & Kim, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found that occupational stress is associated with presenteeism, which is consistent with the results of previous studies (Chun & Song, 2020;Umann et al, 2014;Yi & Kim, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Cronbach's alpha for the entire scale was .84 in a previous study (Chun & Song, 2020) and .82 in this study.…”
Section: Presenteeism Was Measured Using the Korean Version Of Thesupporting
confidence: 59%
“…Due to the features of nurse work, such as shiftwork, inflexible work schedules, prolonged working time, and heavy workloads [ 10 , 11 , 12 ], nurses face extremely high stress, which not only harms their health but also decreases their productivity and keeps them from performing their jobs effectively in the workplace [ 12 , 13 ]. Previous studies have suggested that occupational stress is a predictor of presenteeism [ 14 , 15 , 16 ], while stressors of different natures may have different effects on individuals [ 17 ]. Cavanaugh separated challenge and hindrance stress based on their natures.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review regarding the value of continuing professional development for recruitment or retention reported that the literature did not contain longitudinal studies and was limited to cross-sectional, exploratory, and descriptive survey designs [ 32 ]. Cross-sectional studies included reports that the nature of the study, even when coupled with advanced statistics, could not establish causal relationships or confirm the directionality of the associations [ 48 , 49 , 50 , 51 , 52 ]. Memory bias was another problem reported by cross-sectional studies, for example, for the measurement of attitudes before and after a program intervention [ 52 ] and conducting a retrospective evaluation of why providers left rural practice [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recommendations for this category came from seven papers. To overcome an over reliance on cross-sectional study designs and to help confirm the causality of the hypothesis raised by cross-sectional studies, more longitudinal research designs should be used [ 50 , 63 , 67 ]. Cohort study designs could monitor the workforce data for underserved areas [ 63 ] and also apply to trajectories over time, such as measuring how willingness for rural practice evolves with students through their occupational therapy education [ 52 ].…”
Section: Resultsmentioning
confidence: 99%